ANALISA PENGARUH NON PERFORMING LOAN ( NPL ), BOPO DAN NET INTEREST MARGIN ( NIM ) TERHADAP RETURN ON ASSET ( ROA ) PADA BANK PERKREDITAN RAKYAT KONVENSIONAL DI JAWA TIMUR - Budiono Budiono (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2017)
This research was conducted at Conventional Rural Bank in East Java period 2009-2012. The purpose of this research is to know the influence of Non Performing Loan (NPL), BOPO, Net Interest Margin (NIM) to Return On Asset (ROA) with sample of 30 banking companies. Problem solving using multiple linear regression analysis techniques. Based on the results of the analysis it is known that the NPL has a significant effect on profitability (ROA). BOPO has a significant effect on profitability (ROA), and NIM has a significant positive effect on profitability (ROA).